Dampak Positif Kurikulum Emosional Pada Perkembangan Emosional Anak Usia Dini - Wijayanti, Catur Menik; Fauzi, Fauzi (Universitas PGRI Semarang, 2024)
AbstractThe emotional curriculum in early childhood has significant importance. The emotional curriculum for early childhood provides meaningful insight into understanding children's emotional and social development over a period of time. This can of course help in deepening understanding of how children understand and manage their emotions, the development of social relationships, and the way they learn in emotional contexts. This research aims to determine the positive impact of the emotional curriculum on the emotional development of early childhood. This type of research is phenomenology with a qualitative approach. Qualitative research is said to be a series of research that is capable of producing data in the form of words, either written or verbal, from objects or human behavior that can be observed. The subjects of this research were Kindergarten students in Sokanegara Village, teachers, school principals and parents in their support for the implementation of the emotional curriculum in early childhood. The data collection techniques used in this research were interviews, observation and documentation. The data analysis technique in this research is through three channels of qualitative data analysis, namely data reduction, data presentation, and drawing conclusions. That to design an emotional curriculum for early childhood is possible through a curriculum of creative games and processes that support children's growth and development in terms of emotional skills. In identifying effective strategies in supporting children's emotional development, the emotional curriculum in early childhood has a significant positive impact. Overall, this research makes a meaningful contribution in increasing understanding, developing effective pedagogy, improving social interactions, and demonstrating the role of positive models for all parties involved in early childhood education.Keywords: curriculum; emotional; early childhoodAbstrakKurikulum emosional pada anak usia dini memiliki kepentingan yang signifikan. Kurikulum emosional pada anak usia dini memberikan wawasan yang bermakna dalam memahami perkembangan emosional dan sosial anak pada satu periode. Hal ini tentu saja dapat membantu dalam memperdalam pemahaman tentang bagaimana anak- anak memahami dan mengelola emosi mereka, perkembangan hubungan sosial, dan cara mereka belajar dalam konteks emosional. Penelitian ini bertujuan untuk mengetahui dampak positif dari kurikulum emosional pada perkembangan emosional anak usia dini.. Jenis Penelitian ini adalah fenomenologi dengan pendekatan kualitatif. Penelitian kualitatif dikatakan sebagai rangkaian penelitian yang mampu menghasilkan data berupa kata- kata, baik secara tertulis ataupun lisan dari objek atau perilaku manusia yang dapat diamati. Subjek penelitian ini adalah siswa/siswi TK Kelurahan Sokanegara, guru, kepala sekolah dan orang tua murid dalam dukungannya terhadap penerapan kurikulum emosional pada anak usia dini.Teknik pengumpulan data yang digunakan pada penelitian ini adalah dengan wawancara, observasi, dan dokumentasi. Teknik analisis data pada penelitian ini adalah melalui tiga jalur analisis data kualitatif, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Bahwa untuk merancang sebuah kurikulum emosional bagi anak usia dini adalah dapat melalui kurikulum permainan kreatif dan proses yang mendukung pertumbuhan dan perkembangan anak- anak dalam hal kecakapan emosional. Dalam mengidentifikasi strategi yang efektif dalam mendukung perkembangan emosional anak, kurikulum emosional pada anak usia dini memiliki dampak positif yang signifikan. Secara keseluruhan penelitian ini memberikan kontribusi yang bermakna dalam meningkatkan pemahaman, pengembangan pedagogi yang efektif, memperbaiki interaksi sosial, dan menunjukkan peran model yang positif bagi semua pihak yang terkibat dalam pendidikan anak usia dini.Kata kunci: kurikulum; emosional; anak usia dini